O conceito de vontade na filosofia moral de Immanuel Kant - Luiz, Ademir (2017)
The goal of this dissertation is study the concept of will in Immanuel Kant’s foundation of Metaphysics of the customs and to explain how he, based in this principle, support the possibility of the determination of the human action by pure practical reason